On the optical properties of mineral dust in ice-cores as revealed by light scattering techniques - Cremonesi, L; Delmonte, B; Ravasio, C; Artoni, C; Potenza, M (2022)
There is much information to be derived from the airborne dust that can be found in ice cores, especially about the aerosol composition and sources, including the characteristics of the atmosphere of several thousands of years ago. There is, in fact, much still to learn about both the data that can be retrieved and how to interpret them with appropriate models. One of the most striking aspects of these tiny particles is the effect their shape alone has on their scattering and absorption properties, which translate into a contribution to the Earth radiative transfer, especially at the wavelength scale. We show that aggregates of several particles behave differently from compact particles, and non-isometric compact particles can be clearly distinguished from isometric particles as their non-sphericity increases. We report the advances in this direction based on light scattering measurements on the dust content of ice cores drilled from Dome C and Dome B in Antarctica as part of the EPICA project, and provide a physical interpretation in terms of the known models in the field of light scattering by small particles.